2019
DOI: 10.1115/1.4045317
|View full text |Cite
|
Sign up to set email alerts
|

An Environment Friendly Approach to Reduce the Breakdown Pressure of High Strength Unconventional Rocks by Cyclic Hydraulic Fracturing

Abstract: Unconventional hydrocarbon resources mostly found in highly stressed, overpressured, and deep formations, where the rock strength and integrity are very high. When fracturing these kinds of rocks, the hydraulic fracturing operation becomes much more challenging and difficult and in some cases reaches to the maximum pumping capacity limits without generating any fracture. This reduces the operational gap to optimally place the hydraulic fractures. Current stimulation methods to reduce the fracture pressures inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…For Tennessee sandstone, the decrease in the breakdown pressure caused by cyclic fracturing can largely be attributed to the reduction in tensile strength due to water saturation 53 . In ultra-tight concrete, the reduction percentage is higher (25%) compared with in low-and medium-strength cement blocks (15%) 55 . This finding on concrete is in line with experiments on Xujiahe sandstone 56 .…”
Section: Discussion Of Field Application and Evidencementioning
confidence: 86%
See 1 more Smart Citation
“…For Tennessee sandstone, the decrease in the breakdown pressure caused by cyclic fracturing can largely be attributed to the reduction in tensile strength due to water saturation 53 . In ultra-tight concrete, the reduction percentage is higher (25%) compared with in low-and medium-strength cement blocks (15%) 55 . This finding on concrete is in line with experiments on Xujiahe sandstone 56 .…”
Section: Discussion Of Field Application and Evidencementioning
confidence: 86%
“…In general, the benefit reported is threefold: First, hydraulicfatigue testing allows the breakdown pressure to be lowered. Laboratory tests of cyclic hydraulic fracturing on Tennessee sandstone 53 , Pocheon granite 49 , Fontainebleau sandstone 54 , and cement-core plugs with variable strength properties 55 have been reported. The percentage of the reported reduction of breakdown pressure varies for different rock types and with the porosity and strength of individual rock types.…”
Section: Discussion Of Field Application and Evidencementioning
confidence: 99%
“…Kang et al [12] Tight Xujiahe sandstone Kang et al [12] Normal Xujiahe sandstone Patel et al [4] Tennessee sandstone Goyal et al [5] Tennessee sandstone Zhuang et al [16,17] Pocheon granite Diaz et al [18,19] Pocheon granite Stephansson et al [20] Pocheon granite Liang et al [21] Concrete Tariq et al [8] Concrete 6 Geofluids where b and σ f ′ are empirically fitted parameters, which are called the fatigue strength exponent and the fatigue strength, respectively. Figure 12 illustrates the concept of the σ a versus N f curve.…”
Section: Authors Rock Typementioning
confidence: 99%
“…Several research groups have experimentally investigated the effect of cyclic loading on breakdown pressure reduction: Patel et al [4] and Goyal et al [5] conducted cyclic injection on sandstone; Zhuang et al [6] and Zang et al [7] conducted cyclic injection on granite; and Tariq et al [8] conducted cyclic injection on concrete. They reported that at laboratory scale, compared to conventional injection in which the injection pressure increases monotonically, the cyclic injection can reduce the breakdown pressure of sandstone [4,5], granite [6,7], and concrete [8]. For example, Zhuang et al [6] conducted cyclic injection tests on 34 Pucheon granite specimens, and they reported that cyclic injection can reduce the breakdown pressure for granitic rocks by at least 10%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation